Firm growth in Europe: An overview based on the CompNet labour module - Cristina Fernández; Roberto García; Paloma Lopez-Garcia; Benedicta Marzinotto; Roberta Serafini; Juuso Vanhala; Ladislav Wintr (European Central Bank (ECB), 2017)
This paper illustrates the main features of the Labour Module of the CompNet dataset which provides indicators of firm growth over the period 1995-2012 across 17 EU (13 euro area) countries and 9 macro-sectors. It also includes information on a large set of micro-aggregated characteristics of firms growing at different speed such as their financial position and labour and total factor productivity. The paper shows that during the Great Recession the share of shrinking firms sharply increased in countries under stress, while firm growth slowed down in non-stressed countries. In the former, the construction sector suffered the most, while in the latter manufacturing and services related to transportation and storage were mainly affected, possibly as a result of the trade collapse. While we find that, all else equal, more productive firms had a higher probability of growing, the process of productivity-enhancing reallocation was muted during the Great Recession.
Keywords: J23; L11; L25; 330; firm growth; micro-aggregated data; cross-country analysis